Structural and functional evaluation of interaction between mammalian ribosomal RNA with platinum-containing antineoplastic drugs - Theile, Dirk; Koš, Martin (Toxicology letters, 2016)
Cisplatin, oxaliplatin, and carboplatin primarily target DNA, but also alter RNA functionality, albeit to different extent. This study determined the in vitro cytotoxicity (IC50 values) of platinum drugs in LS180 cells and compared the rRNA platination patterns following IC50 exposure. Relevance of particular secondary RNA structures for platination susceptibility was evaluated by primer extension methodology using 18S rRNA as a model RNA. Consequences of rRNA platination for translation efficiency were evaluated by monitoring fluorescence of a destabilised green fluorescent protein variant through flow cytometry. Oxaliplatin and cisplatin were most cytotoxic with IC50 values of 1.7μM±0.8 and 4.1μM±0.1, respectively. Carboplatin was significantly less efficient (IC50 147.1μM±19.4). When exposed to equitoxic concentrations (respective IC50), all three compounds caused similar stop signal incidence or intensity. Moreover, the same rRNA sites were targeted without selectivity for particular secondary structures but with a slight preference for guanine-rich regions. Compared to cycloheximide, none of the drugs diminished translation efficiency at typical in vivo concentrations. In conclusion, equitoxic concentrations of platinum drugs target the same sites in cellular rRNA and cause similar platination intensities. At pharmacokinetically relevant concentrations, cisplatin, oxaliplatin or carboplatin do not inhibit translation efficiency.